2017
DOI: 10.1002/ejic.201601419
|View full text |Cite
|
Sign up to set email alerts
|

Precursors for p‐Type Nickel Oxide: Atmospheric‐Pressure Metal–Organic Chemical‐Vapour Deposition (MOCVD) of Nickel Oxide Thin Films with High Work Functions

Abstract: A series of unsymmetrical nickel -diketonate derivatives have been synthesised and structurally characterised for application as atmospheric-pressure metal-organic chemical vapour deposition (AP-MOCVD) precursors for nickel oxide.[a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…There are very few suitable Ni precursors to choose from, and the commonly used Ni precursors include highly toxic carbonyls, the comparably unreactive nickelocene, , and nickel acetylacetonate , that often require plasma or ozone as co-reactant. Cosham et al proposed nickel acetylacetonate derivatives and amine adducts as precursors for atmospheric pressure CVD, but they needed high evaporation temperatures . This may be circumvented by fluorinated side chains, which suppress intermolecular interactions, as shown by Malandrino et al , Recently, rationally designed precursors like amino alkoxides and guanidinates have been explored …”
Section: Introductionmentioning
confidence: 99%
“…There are very few suitable Ni precursors to choose from, and the commonly used Ni precursors include highly toxic carbonyls, the comparably unreactive nickelocene, , and nickel acetylacetonate , that often require plasma or ozone as co-reactant. Cosham et al proposed nickel acetylacetonate derivatives and amine adducts as precursors for atmospheric pressure CVD, but they needed high evaporation temperatures . This may be circumvented by fluorinated side chains, which suppress intermolecular interactions, as shown by Malandrino et al , Recently, rationally designed precursors like amino alkoxides and guanidinates have been explored …”
Section: Introductionmentioning
confidence: 99%
“…O 2 plasma treatments are less sensitive to the specific operating conditions than annealing. For example, Ullrich et al observed an increase in the work function of solution‐processed NiO x films from 4.4‐4.9 eV to 5.5‐5.6 eV with a 1‐minute oxygen plasma treatment with 900 W plasma power at 0.3 mbar pressure, 139 while a similar increase from 4.4 to 5.5 eV in APMOCVD NiO x films was achieved also after a 3 minutes treatment with 100 W plasma power 147 …”
Section: Post‐deposition Processingmentioning
confidence: 92%
“…The additional advantage of the plasma treatment is the change in the surface wettability, which can enable the solution processing of additional layers on top of the NiO x . 145,146 Oxygen plasma treatment is also commonly used to increase the work function of the films, and its effect, attributed to the increase in Ni vacancies as well as to the formation of NiOOH species has been well documented for films deposited by various techniques 79,139,146‐148 . O 2 plasma treatments are less sensitive to the specific operating conditions than annealing.…”
Section: Post‐deposition Processingmentioning
confidence: 99%
See 2 more Smart Citations